Why do bank risks affect stock returns? Examining the mediating role of profitability in Indonesia’s tier-1 banks‎ - Gunawan, Indri; Soma , Abdul Mukti (Universitas Islam Indonesia, 2025)
IntroductionSmall-scale Indonesian banks face intense challenges following the implementation of the ASEAN Economic Community and domestic capital requirements. While profitability is shaped by credit risk, operational efficiency, and capital adequacy, the translation of these internal factors into stock returns remains uncertain. Islamic banks, with their unique risk-sharing principles, offer a distinct context for evaluating this relationship.ObjectivesThis study investigates whether credit risk, operational efficiency, capital adequacy, and net interest margins influence stock returns in small Indonesian banks, and whether profitability, measured by return on assets, mediates this relationship within the framework of Islamic banking principles.MethodThe research applies a quantitative panel analysis of 15 listed small-scale Indonesian banks from 2014 to 2022. Financial and market data were drawn from official regulatory and market reports. Feasible generalized least squares with panel-corrected standard errors, alongside trimming and winsorization techniques, were employed to address heteroskedasticity, autocorrelation, and outliers.ResultsThe findings demonstrate that credit risk and operational inefficiency reduce profitability, while net interest margins increase it. Capital adequacy shows no significant impact on profitability. However, none of these factors, including profitability itself, significantly explain stock returns, which appear dominated by external drivers such as macroeconomic variables and investor sentiment. Profitability does not mediate the relationship between risk factors and stock performance.ImplicationsThe results highlight a disconnection between internal performance measures and market outcomes in small Islamic banks. For theory, the study challenges conventional risk-return models by emphasizing institutional and behavioral factors. For practice and policy, the findings underline the need for improved risk management, operational efficiency, transparency, and investor education to strengthen the link between profitability and shareholder value.Originality/NoveltyThis study contributes to the literature by integrating risk-return analysis with the specific context of Islamic banking. It shows how profitability drivers in small banks do not automatically translate into equity market performance, underscoring the importance of governance, Shariah compliance, and investor sentiment in shaping financial sustainability.